A semente de Passiflora edulis Sims f. flavicarpa O. Deg. (Maracujá-Amarelo) durante a germinação e crescimento inicial da plântula: a dinâmica de lipídios, carboidratos e cloroplastos, e sua relevância nesse período - Tozzi, Henrique Hespanhol [UNESP] (2014)
Seed reserve mobilization in Passiflora edulis fruit is of great importance to the knowledge of this species seed germination, and this knowledge can open new ways for scientific and economic applications. Our experiments showed seed reserve mobilization through transmission electron microscopy, where we observed the disposition of the lipid bodies, protein bodies consumption and subsequent vacuole formation, and evidence of metabolism resumption with changes in nuclei format. We also analyzed free fatty acids during germination, verifying that there are differences in fatty acid mobilization between the continuous light and darkness treatments, in the endosperm. In the cotyledons, there are no significant differences between the two treatments, suggesting that the differences in the patterns of reserve mobilization may have an important role in maintaining the cotyledons in the same developmental stage in continuous light as well as in darkness. Free sugar analysis showed an erratic consumption pattern for some sugars in the endosperm, presenting increment/mobilization cycles in continuous light as well as continuous darkness, whereas in the cotyledons, with little to no variation in the first days after sowing (DAS) followed by an increase in averages at 8 and 10 DAS. We also observed the presence of chloroplasts in the endosperm of seeds germinated under continuous white light, and in the cotyledons of seeds germinated under continuous white light and continuous darkness. The endosperm of an orthodox seed having chloroplasts is still not reported in the literature, and analysis to verify their morphology and similarity to photosynthesizing chloroplasts, as well as its importance in the endosperm, are of great relevance. We also tried to show the endosperm role in the plant initial development, and possible differences in plant growth and development during the initial days of establishment. These differences can be explained not only...